COMPREHENSIVE ANALYSIS OF INTELLIGENT TECHNOLOGICAL FRAMEWORKS ENHANCING WOMEN’S SAFETY AND SECURITY APPLICATIONS - Patil, Harshali; Tiwari, Arya Brijesh; Singh, Kinjal Prithviraj; Singh, Anant Manish (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Social beliefs on women’s rights and historical trends of gender-based violence have had a big impact on how women’s safety and security apps have developed. Women all around the world have endured centuries of discrimination and abuse and their vulnerabilities in both public and private settings are well acknowledged. In the contemporary era, women are no longer regarded as a marginalized group. They hold equal authority, rights and opportunities alongside men making significant contributions across various fields thereby fostering global progress. Despite these advancements, gender- based challenges persist, particularly in developing and underdeveloped regions. In an ever-changing technology context, ongoing research and development efforts are required to produce inclusive safety apps that take into consideration the varied experiences of all women, guaranteeing that these tools are reliable and successful in boosting their safety and security. One of the most pressing concerns is the persistent threat of physical harassment which hinders women’s empowerment and societal participation. This study conducts an extensive review of existing frameworks and technological innovations in the domain of women’s safety. A comparative evaluation of multiple security-oriented technologies including the Internet of Things (IoT), Embedded Systems, Artificial Intelligence (AI), Machine Learning (ML), Augmented Reality (AR) and mobile-based applications has been undertaken to assess their effectiveness in ensuring women’s safety. The global market for women’s safety software is anticipated to grow at a compound annual growth rate (CAGR) of 5.6% between 2024 and 2032. With over 700 million internet users and 600 million smartphone users, there is a substantial base for digital solutions aimed at enhancing women’s safety, The effectiveness and limits of current women’s security apps and new technologies are carefully evaluated in this study using a structured qualitative method. The findings highlight potential research gaps and propose critical directions for future advancements aiming to aid researchers in developing a holistic security solution that ensures a safer environment for women on a global scale.